(The facilitative approach to the morphological rules of the Algerian mark al- Tayeb al- Mahaji Through his manuscript (Mabadi Al- Sirf - Abdel Rahman, Fatima (Journal of Humanities & Social Sciences, 2019)
The scientistes have confirmed that the morphology is the mother of languages and the grammar is the father as a science concerned with the search for the provisions of the structure of words and letters of originality and increase, health, and the other and approved and studied to study the Arabic language, which is understood from the Koran, scientists have tried to facilitate and adopted a methodology and easy way to understand this beginner The material morphological and entrenched in his mind and this is what we find in The Tayeb Almhaji in the literalauthor of the (Mabadi Al- Sirf), which simplifies and facilitated the rules of morphology and make it available to the beginner, whois the Algerian good Mark Alhaji, and whatis the methodology in his book (Mabadi Al- Sirf)? Are these rules really helpful and purposeful?